THE IMPORTANCE OF MANAGEMENT INTERNET TECHNOLOGIES IN BUSINESS (Development Service Industry Management, 2025)
The article examines the importance and role of managerial Internet technologies in business as a key digital tool for optimizing management processes to increase the efficiency of an enterprise in any field of activity. It is emphasized that the importance of Internet technologies is manifested in the systemic understanding of information, communication technologies and various services, based on which managerial activities are carried out on the Internet. The percentage of the number of enterprises using ERP, CRM and BI software for business is given. It is considered that managerial Internet technologies cover a wide range of tools, including enterprise resource management systems (ERP), customer relationship management systems (CRM), supply chain management systems (SCM), business analytics (BI), cloud servers and project management tools. It is emphasized that the use of Internet capabilities is manifested in the potential impact on control, coordination and interaction with customers using Internet technologies, which play a key role in modern business. It is found that the above advantages of using Internet technology in business are becoming essential for the formation of a modern vision of the enterprise's activities. Successful digital transformation depends not only on technical implementations, but also on factors such as organizational culture, management approaches, and the ability of enterprises to adapt to change. It is argued that thanks to managerial Internet technologies, it is possible to implement a new concept of organizing processes in business with access to all the information necessary for performing their professional functions using the Internet.
Keywords: management; Internet technologies; business; processes; environment; enterprise